2020
DOI: 10.1029/2019jf005256
|View full text |Cite
|
Sign up to set email alerts
|

Water Tracks Enhance Water Flow Above Permafrost in Upland Arctic Alaska Hillslopes

Abstract: Upland permafrost regions occupy approximately one third of the Arctic landscape. In upland regions, hydrologic fluxes are influenced by water tracks, curvilinear features on hillslopes that preferentially fill with and route water in response to snowmelt and rainfall when the soil above continuous permafrost thaws in the summer. As continued warming of the Arctic may alter hydrologic cycling leading to increased frequency of extreme hydrologic events like drought and flooding as well as modification of biogeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 111 publications
2
40
0
Order By: Relevance
“…Most cryohydrogeologic codes cited in Table 1 offer the option of creating three‐dimensional models, which may be required to understand the potential effect of heterogeneity (Painter et al, 2016). Three‐dimensional models have been applied before (e.g., Evans et al, 2020; Jan, Coon, & Painter, 2019; Karra et al, 2014; Langford et al, 2019) and the theory behind them does not differ from two‐dimensional models. However, due to the lack of developed graphical user interfaces for most cryohydrogeologic modeling tools, three‐dimensional models can be challenging to create and parameterize.…”
Section: Model Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cryohydrogeologic codes cited in Table 1 offer the option of creating three‐dimensional models, which may be required to understand the potential effect of heterogeneity (Painter et al, 2016). Three‐dimensional models have been applied before (e.g., Evans et al, 2020; Jan, Coon, & Painter, 2019; Karra et al, 2014; Langford et al, 2019) and the theory behind them does not differ from two‐dimensional models. However, due to the lack of developed graphical user interfaces for most cryohydrogeologic modeling tools, three‐dimensional models can be challenging to create and parameterize.…”
Section: Model Setupmentioning
confidence: 99%
“…Most of the studies that use these models have considered archetypical cold hydrogeological environments, with the objective of developing a conceptual understanding of these complex settings and how they respond to warming (e.g., Bense et al, 2012; Frampton, Painter, & Destouni, 2013). Research efforts to date have highlighted the importance of heat advection through groundwater flow as a possible contributor to permafrost degradation in certain settings (Dagenais, Molson, Lemieux, Fortier, & Therrien, 2020; McKenzie & Voss, 2013; Shojae Ghias, Therrien, Molson, & Lemieux, 2018; Sjöberg et al, 2016), elucidated the formation and hydrogeological impact of lateral and vertical taliks (Jafarov et al, 2018; Lamontagne‐Hallé, McKenzie, Kurylyk, & Zipper, 2018; Rowland, Travis, & Wilson, 2011; Wellman, Voss, & Walvoord, 2013), illustrated the current and future patterns of groundwater discharge to streams (Evans, Ge, Voss, & Molotch, 2018; Evans, Godsey, Rushlow, & Voss, 2020; Huang et al, 2020; Lamontagne‐Hallé et al, 2018), and to a very limited extent presented field applications of these models (e.g., Dagenais et al, 2020; Evans et al, 2020; Kurylyk, Hayashi, Quinton, McKenzie, & Voss, 2016; Langford, Schincariol, Nagare, Quinton, & Mohammed, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Calcium is sourced from deeper soil horizons (Keller et al, 2007), and concentration typically increases in water tracks as the thaw season progresses (Figure S3). Further, hydrologic models confirm increasing contribution of groundwater to flow in water tracks as the thaw season progresses (Evans et al, 2020). The observed negative correlation of CO 2 with precipitation could indicate that supply of CO 2 to water tracks is limited, if soil CO 2 is flushed from soils and depleted during storms.…”
Section: Discussionmentioning
confidence: 94%
“…Longitudinal patterns in C chemistry coincided with a downslope increase in discharge ( Figure 5) and suggested that dissolved CO 2 is primarily derived from shallow soils. DOC yields from tundra soils are typically greatest from shallow, organic-rich horizons (organic soil depth~20 cm in water tracks; Evans et al, 2020) and decline with depth due to declining organic content of soils, increased time for DOC degradation, and sorption of organic matter to mineral particles (Kawahigashi et al, 2006;Striegl et al, 2005;Uhlirova et al, 2007). The observed longitudinal decline in DOC concentration therefore suggests decreased contribution of shallow relative to deeper flow paths ( Figure 5).…”
Section: Vertical and Longitudinal Patternsmentioning
confidence: 99%
See 1 more Smart Citation